Case Report: Klippel-Trénaunay-Weber syndrome - Victor Parreira Bizinoto; André de Oliveira Martins; Adriana Santa Cecília Borges; Maria Aparecida Lima; Julio Dante Bonetti (Revista Brasileira de Cirurgia Plástica, 2018)
Introduction: The Klippel-Trénaunay-Weber syndrome (KTWS) is characterized by several signs, including capillary malformations and venous malformations with or without lymphatic malformations associated with limb overgrowth. In most cases, only one extremity is involved with arteriovenous malformation, and approximately 75% of the patients manifest symptoms before 10 years of age. Case Report: We report a case of a 7-month-old patient with KTWS followed-up at the Plastic Surgery Service of the Hospital de Clínicas, Federal University of Uberlândia; surgical treatment of the lesion was proposed for the patient. Conclusion: Since KTWS is a progressive disease with severe morbidity, the patient must be followed-up at a reference center by experienced staff with diverse therapeutic arsenal.